KICS: A Model of Motivational Leadership in Organizations - Ugoani, John N. N. (2015)
This pure research gave birth to a Model of Motivational Leadership – KICS: which embraces knowledge, intelligence, collaboration and synergy. It is a synergistic  proposition based on the theory of emotional intelligence as the index of competencies needed for effective leadership. It opened with a general discussion on traditional models of leadership, then the roles of knowledge, intelligence, collaboration and synergy as they relate to motivational leadership. Issues of emotional intelligence clusters and synthesis of the model’s elements were discussed, emphasizing how KICS-based motivational leadership skills can be developed and sustained. Motivational leadership entails exciting people’s imaginations and inspiring them to move in a desired direction. It takes more than simple power to motivate and lead in organizations. Realizing that unity and cohesiveness are built from personal bonds, the best leaders ensure to deepen their rapport with employees and colleagues which enhances organizational performance. This pure research argues that the synergy of related emotional intelligence competencies can lead to motivational leadership behaviour. Knowledge is critical to leadership because there are different types of leadership and different situations require different kinds of knowledge, and the person possessing the knowledge demanded by a certain situation in most cases, tends to become the best leader. A knowledgeable person is one who is trained to consider his actions to undertake them deliberately, in a disciplined manner. Added to this ability is the intelligence to endure in a chosen course in the face of distraction, confusion and difficulty, all combined in producing a motivational leader. Knowledge tends to be procedural in nature and to operate outside of focal awareness. It also reflects the structure of the situation more closely than it does in the structure of formal disciplinary knowledge. The survey research design was used for the study. Data generated were used to describe the KICS Model of Motivational Leadership.